[OA117] Improvements and challenges in postgraduate radiation protection training for dental staff. (August 2018) - Hart, Graham
Abstract : Purpose: Dental practitioners and other registered dental care professionals in the UK undergo regular update training on radiation protection matters as part of their CPD requirement. If assessments are not made as part of the update training session, it is difficult to demonstrate that real learning has taken place. It is also difficult to know whether there are areas of the training that prove difficult for participants to understand. The purpose of the study is to see whether this situation can be improved by the use of both pre-and post- training session testing. Methods: Training sessions for dental practitioners and other registered dental care professionals were provided by the author as a series of 5, 1-h lectures designed to cover a defined syllabus. Prior to the start of the training session, participants completed a short 10-question multiple-choice questionnaire (MCQ). At the end of the session, participants then completed a longer 30-question MCQ. The questions on the pre-session test were a sub-set of the post-session test. Many questions on both tests were designed to have more than one correct answer, and participants were informed of this beforehand, both on the test sheets and by verbal reminder. No fixed time limit was given for the completion of the questionnaires. The pre- and post-training session MCQs have been used at eight training sessions with a total of approximately two hundred participants. Results: > 85% of participants demonstrated an increase in their percentage test scores, with a mean increase in percentage score of 18%. Differences between pre- and post- course test scores were significant at p < 0.01, assessed using the Wilcoxon Rank-sum test. Individual question scores were also analysed and demonstrated that certain questions generated more incorrect answers than others. Conclusions: The use of both pre- and post-course testing for dental radiation training courses can demonstrate that learning has been effective. The analysis of individual question scores can shine a light on those areas where learning has not been as effective and thus help with the delivery of future courses.